Role of enzymes in soil - J, Bayarmaa; D, Purev (Mongolian Journal of Agricultural Sciences, 2018)
Enzymes are an integral part of the soil and their activity is closely related to the physical, chemical and biological properties of the soil. Human activities, intensive agriculture, changes in ecosystem, environmental pollution have a great influence on the activity of soil enzymes. Depending on the origin soil enzymes are indicators for accessing the condition of the soil for short and long period of time. Almost all anthropogenic and environmental factors affecting the physical and chemical properties of the soil are studied for this purpose, but enzymes in the soil are the most sensitive to these changes. So it is a time to the study of the enzymes in the soil.